Long- and short-lived radiogenic isotope constraints on the history of the early Earth and the Moon - Hasenstab, Eric (2022)
The only known habitable planet is the Earth. As geological processes are what led to Earth's habitability, understanding Earth’s geodynamic evolution is of crucial importance. However, the geodynamic processes of the early Earth, during the Hadean (>4.0Ga), remain enigmatic. This is a consequence of Earth’s accessible rock record beginning as late as in the Eoarchean, more than 500 Ma after Earth has accreted. Unraveling Earth’s earliest processes therefore requires indirect methods such as isotope systematics. Variations in the isotope composition of short-lived decay systems such as 129I-129Xe, 146Sm-142Nd, or 182Hf-182W have provided strong evidence that substantial geodynamic processes on Earth (e.g. silicate differentiation) already operated during the Hadean. Constraints on Hadean geodynamics are further corroborated by long-lived 176Lu-176Hf and 147Sm-143Nd isotope systematics that support a complex and active history for the infant Earth. Evidence for such a vigorous early planetary evolution is found not only on Earth but also on our closest neighbor, the Moon. Although lunar research has shown that Earth and Moon must be closely related in terms of the material from which it accreted, it remains highly debated if these planetary bodies are chondritic or not. This study investigates the differentiation history of the Earth-Moon system. In three chapters, we report the isotope compositions of various long- and short-lived decay series for 3.53 to 2.63 Ga Archean rocks from the Pilbara Craton (138La-138Ce, 147-143Nd and 176Lu- 176Hf, Chapter I), ~3.8 to 2.0 Ga rocks from SW Greenland (147,146Sm-143,142Nd and 176Lu- 176Hf, Chapter II) and 4.4 to 3.1 Ga lunar rocks (138La-138Ce and 147Sm-143Nd, Chapter III). In rocks from the Pilbara Craton, Ce-Nd-Hf isotope compositions are strongly coupled and yield correlations that are similar to those observed in modern mantle-derived rocks. However, a few ultramafic rocks reveal decoupled Hf-Nd isotope compositions, where extremely high εHf(i) values but only ...